(3TQM NGJeI GdSdes - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s ((3GdeSjM Hf eMeO Hf Ydi s)
(3ChdgG (B:s
(3NGJeI hHYO ai eGOI GdfGXe QMeg Gddg s
(3BNQgG (B:s
(3Gddge fhQ bdhHfG HfG fhQJ Hg bdhH hGNJe dfG HGdSYGOI s
(3GdSde GdeQhfb GfXQ cTa GdXfhf L(B2 (3U` (B998s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
Keywords: (3GdadSaI hGdefWbs